PENGEMBANGAN LKS PRAKTIKUM INSEKTA BERBASIS DIAGRAM VEE UNTUK MENGURANGI BEBAN KOGNITIF SISWA SMA KELAS X - Yuli Arnita Sari; Indra Drajat Sopwan (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2021)
Insect is one of subject matter that has many concepts. In addition, the lack of teaching materials in the form of practicum worksheet that can make learning more meaningful and provide special skills for students. This will cause the emergence of cognitive load for students. Efforts to reduce the cognitive load on students is by developing a worksheet based on Vee diagram. The purpose of this research is to develop insect practicum worksheet based on Vee diagram to reduce the cognitive load of class X high school students, analyze the cognitive load and analyze the responses of teachers and students to insect practicum worksheet based on Vee diagram. This study uses a 4-D model (define, design, develop, and disseminate). The sampling technique of this study used purposive random sampling. Data collection techniques, including: tests, readability and feasibility rubrics, and questionnaire techniques. The study was conducted in SMA NU Widasari Indramayu. The percentage of overall validation is 96.09%, which means that insects practicum worksheet based on Vee diagram are very feasible to be used in the learning process. There is a decrease in cognitive load and positive student responses after developing the insects practicum worksheet.